2010
DOI: 10.2136/vzj2008.0152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pipe Pressurization on the Discharge of a Tile Drainage System

Abstract: Predicting the drainage impacts on downstream peak events is complex because it involves studying many physical processes at different interdependent scales: the individual field, the drainage network, and the catchment. This study focused on an experiment performed in a small subsurface‐drained catchment (130 ha), east of Paris, France. The main objective was to study the influence of the temporary pipe pressurization of the drainage network on the field drainage discharge during intense rainfall events. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…From a hydraulic perspective, drainage discharge is regulated not only by the upper boundary conditions, such as rainfall and evapotranspiration, but also by the pressure conditions in the collector pipes (Henine et al, 2010). In cases of pressurization (i.e., when a positive head builds up in the drainage system because of intensive rainfall or backwater effects), discharge is limited or even reversed.…”
Section: Contents Of the Special Sectionmentioning
confidence: 99%
“…From a hydraulic perspective, drainage discharge is regulated not only by the upper boundary conditions, such as rainfall and evapotranspiration, but also by the pressure conditions in the collector pipes (Henine et al, 2010). In cases of pressurization (i.e., when a positive head builds up in the drainage system because of intensive rainfall or backwater effects), discharge is limited or even reversed.…”
Section: Contents Of the Special Sectionmentioning
confidence: 99%
“…The regime from the relation Q spe f(RP) is characterized by two different linear regimes split by a breaking point close to 2 years, due to design criteria in order to intercept a rainfall of 15 mm d −1 (Augeard et al, 2008;Henine et al, 2012). Above this value, the pipe is pressurized (Henine et al, 2010) and the specific discharge may be strongly reduced (Nedelec, 2005;Henine et al, 2012), according to the size of the networks and depending on the intensity of the event. If the RP of the breaking point decreases, the size of the networks might be considered as no longer suitable to fulfil efficiently their flood protection function.…”
Section: Hydrological Indicators Of Subsurface Drainagementioning
confidence: 99%
“…Compared to undrained cropland, tile drainage also causes significant changes in watershed hydrology 4 , 5 . Studies have shown subsurface drainage removes excess water from the rootzone 6 , results in higher infiltration and lower surface runoff 7 , peak flows 8 and flooding 9 . Tile drainage tends to increase the watershed baseflow 10 , 11 , decrease groundwater travel times 10 , 12 , increase annual runoff volume 4 , 13 16 , and increase instream nitrate concentrations 4 , 8 , 17 , 18 .…”
Section: Background and Summarymentioning
confidence: 99%